Regulation of human methylenetetrahydrofolate reductase by phosphorylation - Yamada, Kazuhiro (National Academy of Sciences, 2005)
Methylenetetrahydrofolate reductase (MTHFR) catalyzes the reduction of methylenetetrahydrofolate to methyltetrahydrofolate, the methyl donor for the conversion of homocysteine to methionine. Regulation of MTHFR activity is crucial for maintaining cellular concentrations of methionine and S-adenosylmethionine (AdoMet). Purified recombinant human MTHFR expressed in insect cells is multiply phosphorylated on an N-terminal extension of the protein that contains a highly conserved serine-rich region. Treatment by alkaline phosphatase removes seven phosphoryl groups from the enzyme. Thr-34 was identified as one of the seven phosphorylation sites by using a monoclonal antibody directed toward (p)Thr-Pro. Mutation of Thr-34 to Ala completely blocks modification as judged by mass spectrometric analysis, suggesting that Thr-34 is the priming phosphorylation site. The Thr34Ala mutant was expressed in baculovirus-infected insect cells, and its enzymic properties were compared with wild-type enzyme. The mutant enzyme and alkaline phosphatase-treated wild-type enzyme are more active than untreated wild-type enzyme and less sensitive to inhibition by saturating AdoMet, indicating that phosphorylation at Thr-34 is critical for allosteric regulation of human MTHFR activity by AdoMet. The absence of methionine and the presence of adenosine in the cell culture medium, which lead to a low intracellular AdoMet/S-adenosylhomocysteine ratio, are associated with faster electrophoretic mobility of MTHFR, presumably because of less or no phosphorylation. Because the faster-mobility MTHFR is associated with the more active form of MTHFR, this response is likely to increase methionine production. Those observations suggest that AdoMet functions not only as an allosteric inhibitor but also to control phosphorylation of human MTHFR.